2019
DOI: 10.1371/journal.pone.0226039
|View full text |Cite
|
Sign up to set email alerts
|

De novo transcriptome analysis and identification of genes associated with immunity, detoxification and energy metabolism from the fat body of the tephritid gall fly, Procecidochares utilis

Abstract: The fat body, a multifunctional organ analogous to the liver and fat tissue of vertebrates, plays an important role in insect life cycles. The fat body is involved in protein storage, energy metabolism, elimination of xenobiotics, and production of immunity regulator-like proteins. However, the molecular mechanism of the fat body’s physiological functions in the tephritid stem gall-forming fly, Procecidochares utilis, are still unknown. In this study, we performed transcriptome analysis of the fat body of P. u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 130 publications
(190 reference statements)
0
4
0
Order By: Relevance
“…CYP enzymes are fundamental elements in insect adaptation due to their role in metabolism and detoxification [ 26 ]. This function is shared especially with the insect-specific Delta and Epsilon classes of GSTs [ 27 ] and with UGTs that play a role in detoxification and resistance by regulating bioactivity and solubility of different compounds [ 28 ]. These genes were similarly overexpressed in media containing alkaloids in both species.…”
Section: Discussionmentioning
confidence: 99%
“…CYP enzymes are fundamental elements in insect adaptation due to their role in metabolism and detoxification [ 26 ]. This function is shared especially with the insect-specific Delta and Epsilon classes of GSTs [ 27 ] and with UGTs that play a role in detoxification and resistance by regulating bioactivity and solubility of different compounds [ 28 ]. These genes were similarly overexpressed in media containing alkaloids in both species.…”
Section: Discussionmentioning
confidence: 99%
“…PA is present in C. bilineata tsingtauica and C. atrata , but the ratios showed that the bioavailability of minerals in these insects is superior to G. max . It is important to note that nutrition is distributed throughout the insect body, including the fat body in the abdomen and beneath the epidermis [ 70 , 71 ]. Based on our results, we advocate that the traditional way of eating C. bilineata tsingtauica in Lianyungang should be changed, and recommend the consumption of the entire larvae as is common in Xuzhou and Shandong.…”
Section: Discussionmentioning
confidence: 99%
“…For example, with this technology, 120 CYP genes were identified in Pardosa pseudoannulata [ 25 ]. Transcriptome analysis of the fat body of Procecidochares utilis revealed many unigenes involved in detoxification, including 50 unigenes of putative CYPs (P450s) in this organism [ 26 ]. We have previously reported 77 unigenes of putative CYPs in G. molesta , which included 13 unigenes in the CYP6 family [ 27 ], the biochemical functions of which are largely associated with the metabolism of xenobiotics [ 21 ].…”
Section: Introductionmentioning
confidence: 99%